IVIG and under Burn Unit Care Yield Favorable Outcomes in Pediatric Patients with Toxic Epidermal Necrolysis: A Case Report and Literature Review - Tareq Z. Alzughayyar; Wasim Noureddin Ibrahim Hamad; Eman A. S. Abuqweider; Bilal Nabeel Mohammad Alqam; Sadi A. Abukhalaf; Rami A. Misk; Fawzy M. Abunejma; Jihad Samer Zalloum; Mohanad Saleh; Ali A. Abumunshar; Yousef I. M. Zatari (Hindawi Limited, 2020)
Body reactions to drugs can manifest as Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). TEN is the most severe form of cutaneous reactions with an incidence rate of 1-2 per million cases per year. Despite TEN being a critical and life-threatening condition, there is little to no evidence of clear management protocol. We reported a 5-year-old male child who presented with lamotrigine-induced TEN and was successfully treated with intravenous immune globulin (IVIG) with a burn unit care level, while TEN treatment with IVIG is an appropriate approach with predictable good outcomes, burn unit care is also effective in creating highly favorable effects. Upon reviewing the literature, several studies indicate that TEN patients treated with the combination of IVIG and burn unit care lead to decreased levels of morbidity and mortality than when treated with IVIG or burn unit care alone. Therefore, treatment involving both IVIG and burn unit care should be considered for TEN patients.